2010
DOI: 10.1073/pnas.1015463107
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for stabilizing superoxide dismutase (SOD1), the protein destabilized in the most common form of familial amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a disorder characterized by the death of both upper and lower motor neurons and by 3-to 5-yr median survival postdiagnosis. The only US Food and Drug Administration-approved drug for the treatment of ALS, Riluzole, has at best, moderate effect on patient survival and quality of life; therefore innovative approaches are needed to combat neurodegenerative disease. Some familial forms of ALS (fALS) have been linked to mutations in the Cu/Zn superoxide dismutase (SOD1). The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 70 publications
3
95
0
Order By: Relevance
“…Dimer destabilization of SOD1 has been implicated in disease progression for amyotrophic lateral sclerosis (ALS) 15, 3336 . Oxygen-modified cysteine residues are negatively charged 37 and if both Cys 111 are oxidized there would be a columbic impetus for destabilizing the SOD1 dimer.…”
Section: Discussionmentioning
confidence: 99%
“…Dimer destabilization of SOD1 has been implicated in disease progression for amyotrophic lateral sclerosis (ALS) 15, 3336 . Oxygen-modified cysteine residues are negatively charged 37 and if both Cys 111 are oxidized there would be a columbic impetus for destabilizing the SOD1 dimer.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the structures of these species would not only allow for definitive testing of their toxicity but could potentially lead to an understanding of disease mechanism and therapeutic strategies against diseases for which no cure or effective treatment exists (22). By their nature, however, these oligomers are only metastable, and therefore difficult to isolate.…”
mentioning
confidence: 99%
“…How should one stabilize the native, benign fold of SOD1? Strategies involving cross-linking (Ray et al 2004;Auclair et al 2010) and ligand binding (Ray et al 2005) have all showed promise of stabilizing the dimer in vitro. None has been tried in vivo yet.…”
Section: A Role For Wild-type Sod1 In Sporadic Alsmentioning
confidence: 99%